The regulatory capacity of B cells directs the aggressiveness of CLL - Mohr, Audrey (Oncoimmunology, 2018)
Chronic lymphocytic leukemia (CLL) is associated with abnormal T-cell responses responsible for defective anti-tumor activities. Intriguingly, CLL B cells share phenotypical characteristics with regulatory B (Breg) cells suggesting that they might negatively control the T-cell activation and immune responses. We elaborated an in vitro co-culture system with T cells to evaluate the Breg capacities of CLL B cells following innate Toll-like receptor 9 (TLR9) engagement. We demonstrated that B cells from half of the patients exhibited regulatory capacities, whilst B cells from the remaining patients were unable to develop a Breg function. The T cell sensitivities of all patients were normal suggesting that defective Breg activities were due to intrinsic CLL B cell deficiencies. Thus, TLR-dedicated gene assays highlighted differential signature of the TLR9 negative regulation pathway between the two groups of patients. Furthermore, correlations of the doubling time of lymphocytosis, the time to first treatment, the mutational status of IgVH and the Breg functions indicate that patients with efficient Breg activities have more aggressive CLL than patients with defective Breg cells. Our in vitro observations may open new approaches for adjusting therapeutic strategies targeting the Breg along with the evolution of the disease.